Discrimination of Neotropical Anopheles species based on molecular and wing geometric morphometric traits (2017)
Morphological similarities among closely related Anopheles helped to confirm species assignation and the geometric morphometric approach revealed wing form differences not only at the subgenera but also at the species level. Each subgenus presented a particular wing size trend, possibly related to the evolutionary history of these